Holocene sedimentary of the Pearl River Delta in South China: OSL and radiocarbon dating of cores from Zhuhai - Lin, Penghui; Xu, Xiaolin; Yan, Chaoyang; Luo, Lan; Abbas, Mahmoud; Lai, Zhongping (Frontiers in Marine Science, 2022)
Deltaic sediments provide a window for investigating delta development processes and the effects of human activities. Despite the fact that numerous studies have been conducted in the Pearl River Delta (PRD), the chronological data are still very limited, which hinder the detailed interpretation of the sedimentary records. The current study aims to establish high-resolution chronology on two cores from Zhuhai using quartz optically stimulated luminescence (OSL) and radiocarbon (14C) dating and, further, to reconstruct the Holocene sedimentary history of the PRD. Core P1-1 has a depth of 79 m and core P3-2 a depth of 60 m. Thirteen quartz OSL samples from P1-1 produced ages between 10.4 and 0.16 ka. Eight OSL and eight 14C ages from P3-2 span from 10.7 to 0.3 ka. The OSL and 14C dates show a good agreement above the depth of 26 m (1.4–0.3 ka), but with discrepancies at depths of 26–54 m. 14C ages (10.7–8.1 ka) are generally older (up to c. 2 ka) than quartz OSL ages, and the discrepancy decreases with depth. The age model shows three phases of the sedimentation process: (1) rapid accumulation rates of 7.48 (P1-1) and 7.52 (P3-2) m/ka between c. 10.7 and 7.5 ka in response to high sea level, (2) followed by a significantly reduced rate of 2.24 m/ka (P1-1) and a depositional hiatus (P3-2) from 7.5 to 2.5 ka as a result of reduced sediment supply and strong scouring by tidal processes, and (3) high sedimentation rates of 8.86 (P1-1) and 9.07 (P3-2) m/ka since 2.5 ka associated with intensive human activities and weakening tidal hydrodynamics. This sedimentary pattern is also evident in many other Asian deltas.